The impact of thermal power stations on coastline and benthic fauna: Case study of El-Burullus power plant in Egypt - Essam A.M. Deabes (Results in Engineering, 2020)
Similar to all the coastal power plants, El-Burullus power plant requires significant amounts of seawater for cooling purposes, where the withdrawn water (6.6 ​m3/Sec) from the Mediterranean Sea circulates through the cooling system and then returns to Sea via the outfall (5.5-m3/Sec). The cooling water has a high temperature and salinity from ambient water at the outfall. The effluents discharge from power plants cause impacts that require investigation or monitoring. Thence, this study was undertaken to evaluate the influence of thermal power plant’s cooling liquid and their structures (intake and outfall) on benthic fauna off the coast of the power plant and the efficiency of the power station, besides the shoreline stability alongshore the west coast of El-Burullus city, Egypt. The study was carried out by numerical modeling and field measurements; the Delft3D-FLOW model is used to examine the thermal and brine plume behavior under various hydrodynamic. The shoreline stability was estimated using the Digital Shoreline Analysis System (DSAS) depending on a time series of shoreline vector data for nine years (2010–2018). Results manifested that the location of the intake pipe head is enough further away from the discharge point to allow for mixing the thermal effluents with the ambient seawater at the outfall and reducing their temperature and salinity before reaching the intake. So, the cooling water recirculation doesn’t affect the operational efficiency of the power plant. El-Burullus station hasn’t any effects on the benthic life organisms which grow far from the outfall site but has negative effects on those lived close to the discharge zone. Also, the morphological results of shoreline revealed that the power plant has slightly negative effects on the stability of the coastline. However, notable erosion occurred on the downdrift side of the outfall (−5.5 ​m/yr), and an accretion occurred on its updraft (9 ​m/yr). As a mitigation, it is recommended to compensate shore eroding at the downdrift side by applying sand bypassing technique.